Kajian Mengenai Stail Kognitif Pelajar dengan Prestasi Akademik Jurusan Teknologi Maklumat - Faziha, Abd. Malek (2004)
The study is on the cognitive style of students of information technology and their academic performance. The cognitive style is studied on the most dominant style used by the students and the institutional influence to the style. The cognitive style influence by institutional and the individual himself. Three types of instructional theories represent three different cognitive styles. Instructional theory of mastery based on the individual ability to master the intellectual skills without any help from other factors. The motivational theory of instruction shows the institutional influence to the style. The institution refers to the environmental input that helps in the development of cognitive style. The structural learning theory shows the structural style. The student depends on himself in this type of cognitive style. These three types of cognitive styles will be seen its relationship with academic performance. In this exploratory study, 135 questionnaires were distributed to the students in third year. The findings have shown the most dominant cognitive style of the students influence by the institution which was the motivational instructional theory. Then it followed by structural style which was the structural learning theory and mastery cognitive style represented by instructional theory of mastery.